2013
DOI: 10.1177/0266666913513277
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of task-technology fit along with attractiveness of alternative technology to utilize RFID system in the organization

Abstract: In spite of exponential growth projections of RFID (Radio Frequency Identification) market value, many companies are reluctant to adopt RFID and RFID vendors are complaining that the business is not growing as fast as expected. The existing challenges and deep skepticism that RFID is facing remains around the return on investment, the incompleteness of RFID technology, and the lack of trust in the result of performance improvement. To fill these voids identified in previous research, from the perspective of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The moderator AA has weakened the positive relationship between PE, EE, SI, FC, PC and ITA but is only significant for PC. This finding is in line with past studies (Kim et al , 2015; Pham and Ho, 2015). Hartono and Wahyono (2018) also demonstrated that consumers switch to alternative products or services if the competitors are perceived to be more attractive, reliable and provide higher quality.…”
Section: Discussionsupporting
confidence: 94%
“…The moderator AA has weakened the positive relationship between PE, EE, SI, FC, PC and ITA but is only significant for PC. This finding is in line with past studies (Kim et al , 2015; Pham and Ho, 2015). Hartono and Wahyono (2018) also demonstrated that consumers switch to alternative products or services if the competitors are perceived to be more attractive, reliable and provide higher quality.…”
Section: Discussionsupporting
confidence: 94%
“…When firms evaluate the worth of a new IS, they compare the perceived utility of the new system with that of the prior system (Besen and Farrell, 1994;Karahanna et al, 1999;Kim et al, 2013). After substituting the RFID system for a barcode system, the RFID system must still be integrated with the prior Web EDI and ERP systems.…”
Section: Discussionmentioning
confidence: 99%
“…Task attractiveness refers to the attraction embedded in the capability green banking services in helping users to complete tasks (Shen et al, 2017). From the perspective of business productivity and efficiency, task attractiveness is an analytic tool for gauging the success of IT adoption (Kim et al, 2015). Following the routes showed by Chen and Shen (2015) and Pappas et al (2017), we hence suggest that only when the capabilities of green banking services will match the task demands of users, the technology may have a positive effect on users' usage intention.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 94%
“…Unlike usefulness, Shankar and Kumari (2016) explore that social influence has the least influence on mobile banking (m-banking) adoption behavior of Indian consumers. According to Kim et al (2015), the fit between the technology and users' tasks affect RFID-driven task performance based on the extended Task-Technology Fit (TTF) model in Korea. In addition, performance expectancy, effort expectancy, and social influence are often reported to be the strongest predictor of behaviour intention and usage behaviour of Internet banking (Martins et al, 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%